(untitled) (Eurasian Medical Research Periodical, 2023)
This report presents description of the clinical characteristics of 61 patients with diagnosis herpesinduced erythema multiforme and the results of the complex therapy with use of antiviral preparations, immunomodulator gosalidone, interferon inductor and hyposensibilizing therapy. The results of the observations showed that after the complex treatment the frequency of recurrences decreased, on the average, two-times, recurrence duration shortened, on the average to 2-4 days, and remission longevity increased, on the average, 1,8-2 times. The use of the developed in Uzbekistan native inductor of interferon gozalidone in the complex therapy herpesinduced erythema multiforme showed marked clinical effect, that allowed increase duration of the clinical remission and shortened longevity of the recurrences. Our observations indicated about perspectives in relation to use of gozalidon in the therapy and prevention of the recurrences in the patients with herpesinduced erythema multiforme.